Racial Equity in Transfer Incentive Policies: A Critical Mixed Methods Analysis - Chrystal A. George Mwangi; Patricia Feraud-King; Ling Chen; Miguel Tejada; Caryn Brause; Kat J. Stephens; Jamina M. Scippio-McFadden; Jeffrey Edelstein; Ryan S. Wells (SAGE Journals, 2022)
Objective/Research Question:
This article examines the racial equity of transfer incentive policies by responding to the research question: How do students of differing races and ethnicities vary in their opportunity to benefit from transfer incentive policies?
Methods:
We utilized a mixed-methods approach, grounded in Critical Race Theory (CRT). This study included an analysis of state policies’ components and mechanisms to consider whether they are grounded in racially unjust assumptions. The critical policy analysis is combined with a QuantCrit analysis of national data from the Beginning Postsecondary Students Longitudinal Study (BPS) to understand how identified aspects of the policies would affect students of differing races/ethnicities.
Results:
Our critical policy discourse analysis demonstrates that states’ transfer incentive policies could foster racial inequity through the requirements students must meet (e.g., full-time status, being under the age of 24) and assumptions about what students may know or need regarding transfer. The QuantCrit analysis revealed that many transfer incentive requirements from the policy analysis findings would have a disproportionately negative effect on racially minoritized students’ transfer eligibility. Together, findings and results illustrate how transfer incentives can contribute to educational inequity for racially minoritized students via color-evasive and meritocratic policies.
Conclusions/Contributions:
Implications include policy reform needed for the development of incentives aligned with closing the racial transfer gap and focused on incentivizing 2- and 4-year institutions in improving the transfer rates of racially minoritized students.
Keywords: Education